CORRECTION OF LEARNING DISORDERS BY OPTIMIZING THE DEVELOPMENT OF SPATIAL AND TEMPORAL ORIENTATION - Denisa BĂLĂNEAN; Eugen BOTA; Simona PETRACOVSCHI (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2021)
Learning to read, write and calculate are proving to be some of the most significant cognitive processes in early education. The objective of this systematic review is to explore the associations between the psychomotor component and the academic achievement in writing, reading, and mathematics. An organized and methodical research of electronic databases was completed in order to determine significant studies. Twenty eligible articles were strictly evaluated, with extracted and summarized keywords. The two components of the psychomotor activity that influence reading were primarily the orientation ability and the fine motor skill, which is the one responsible for the correct spelling of “mirror-writing”. Differences in motor function were observed after intervention programmes. The results of all researchers have shown that there is a link between dysgraphia, dyslexia and the orientation ability or visual perception. Meanwhile, the role of cognitive and motor skills that underpinned mathematical performance was highlighted, and children who had a high capacity for spatial and visual orientation benefited from a better understanding and perception of geometric figures. However, the importance of students' spatial reasoning in relation to mathematics was identified, but only in terms of geometry. Poor quality of spatial notions has been found to be one of the causes of delay in the acquisition of reading, writing and mathematical calculation. The role of fine motor skills in the writing process was also noted, being of real importance in times when the child manipulates the writing tool and puts a word or a sentence on the page.